Quantification of thymol content in different extracts of Zataria multiflora by HPLC method - Azar Aghamohammadi; Mohammad Azadbakht; Seyed Jalal Hosseinimehr (Mazandaran University of Medical Sciences, 2016)
Zataria multiflora Boiss is used in traditional folk remedies as antiseptic, analgesic, carminative, anthelmintic medication. The main components of Z. multiflora are phenolic compounds such as thymol and carvacrol. The aim of this study was developed a simple and rapid method for determination of the thymol in different extracts of Z. multiflora by HPLC method. The dried aerial parts of Z. multiflora in the flowering stage was extracted with ethanol 34%, 42% and 70% for 48 hours. Several mobile phase systems were applied for development and separation of thymol and carvacrol that have close retention time in HPLC system. The peaks of thymol and carvacrol are successfully separated in acetonitrile-water-acetic acid mobile phase. Thymol and carvacrol were separated with a retention times 10.4 and 9.8 minutes respectively, in an isocratic solvent system with HPLC. Thymol content was 2.7 ± 0.06, 3.7 ± 0.07 and 6.0 ± 0.11 mg/g, in ethanol at concentration of 34%, 42% and 70%, respectively. Thymol content in different hydroalcoholic extract of Z. multiflora is dependent to ethanol concentration in extraction solvent.